Structural Features of Lignin Fractionated From Industrial Furfural Residue Using Alkaline Cooking Technology and Its Antioxidant Performance - Li, Rui; Wang, Xiaohui; Lin, Qixuan; Yue, Fengxia; Liu, Chuanfu; Wang, Xiaoying; Ren, Junli (Frontiers in Energy Research, 2020)
Abstract ： For furfural industry, industrial furfural residue as the solid waste was generated from the production of furfural, and is rich in cellulose and lignin with a certain degree of degradation because of strong acid (H2SO4) as catalyst. In this work, alkali cooking technology was applied to extract lignin from industrial furfural residue to explore the new route of industrial application. The effect of different alkali treatment conditions on the chemical structure of lignin was studied. And the effects of different alkali treatment conditions on the composition and chemical structure of the residue were studied by NREL, 13 C NMR and ATR. The results showed that obtained lignin contained abundant guaiacyl (G), syringyl (S) and p-hydroxyphenyl (H) structural units, among which G-type lignin structural units accounted for the main proportion. The extracted lignin samples were rich in hydroxyl, and the highest content of hydroxyl was 4.02 mM/g under the condition of alkali cooking (135 ℃-0.35 M). Oxidize resistance test showed obtained lignin samples had high inhibition effect on DPPH. Moreover, the relative content of cellulose in the solid residue decreased and the relative content of lignin increased significantly because of the lignin-like substance formation by partial degradation and carbonization of cellulose under high-severity cooking treatment. This alkali cooking technology was suitable for extracting lignin from furfural residue without significant change in lignin structure, which have the promising application as potential antioxidants in food and cosmetics.